Sociology today social transformations in a globalizing world (SAGE studies in international sociology)
This collection effectively mirrors the diversity and variety of transformations underway in today's societies and transnational spaces. It offers a cutting edge understanding of what is happening in our life worlds, work lives and frames of social existence